Protective antitumor immunity induced by tumor cell lysates conjugated with diphtheria toxin and adjuvant epitope in mouse breast tumor models - Wang, Ze-Yu; Xing, Yun; Liu, Bin; Lu, Lei; Huang, Xiao; Ge, Chi-Yu; Yao, Wen-Jun; Xu, Mao-Lei; Gao, Zhen-Qiu; Cao, Rong-Yue; Wu, Jie; Li, Tai-Ming; et al. (Ai zheng, 2012)
Cancer cell vaccine-based immunotherapy has received increasing interest in many clinical trials involving patients with breast cancer. Combining with appropriate adjuvants can enhance the weak immunogenic properties of tumor cell lysates （TCL）. In this study, diphtheria toxin （DT） and two tandem repeats of mycobacterial heat shock protein 70 （mHSP70） fragment 407-426 （M2） were conjugated to TCL with glutaraldehyde, and the constructed cancer cell vaccine was named DT-TCL-M2. Subcutaneous injection of DT-TCL-M2 in mice effectively elicited tumor-specific polyclonal immune responses, including humoral and cellular immune responses. High levels of antibodies against TCL were detected in the serum of immunized mice with ELISA and verified with Western blot analyses. The splenocytes from immunized mice showed potent cytotoxicity on EhrUch ascites carcinoma cells. Moreover, the protective antitumor immunity induced by DT-TCL-M2 inhibited tumor growth in a mouse breast tumor model. DT- TCL-M2 also attenuated tumor-induced angiogenesis and slowed tumor growth in a mouse intradermal tumor model. These findings demonstrate that TCL conjugated with appropriate adjuvants induced effective antitumor immunity in vivo. Improvements in potency could further make cancer cell vaccines a useful and safe method for preventing cancer recurrence after resection.